Narasi Korban Perkosaan pada Pemberitaan di Media Daring RRI Samarinda: Analisis Wacana Kritis Model Sara Mills - Nina Queena Hadi Putri; Firstya Evi Dianastiti; Sumarlam Sumarlam (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Cases of violence against children in the East Kalimantan region have reached 1,386 complaints since 2019. Through critical discourse, it can be seen how the language of the media conveys information to readers through the emphasis on actors positioned in the text. This qualitative descriptive research emphasizes documentary analysis by reviewing published written sources, namely the news entitled “Kisah Pilu Korban Pemerkosaan Dipaksa Menikah dengan Pelaku”. Based on the discourse strategy used by the author, it can be seen that this “heartbreaking story of a rape victim” becomes the object of the story. It is evidenced by the use of markers such as a child, sexual violence, forced marriage, rape, exacerbating trauma, and the victim getting worse. The news is presented based on events that emerged because of the description of other actors as the storyteller's subject, not based on the victim's information about what he experienced. The news text reveals a picture of the position of the subject and the object of the story so that it can determine the way the text is presented to the reader. The news text contains a gender bias because the incident is not told from the perspective of women as victims.